Conceptual modeling 31st International Conference ER 2012, Florence, Italy, October 15-18, 2012. Proceedings - Cheung, David; Ram, Sudha; Atzeni, Paolo (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 31st International Conference on Conceptual Modeling, ER 2012, held in Florence, Italy, in October 2012. The 24 regular papers presented together with 13 short papers, 6 poster papers and 3 keynotes were carefully reviewed and selected from 141 submissions. The papers are organized in topical sections on understandability and cognitive approaches; conceptual modeling for datawarehousing and business intelligence; extraction, discovery and clustering; search and documents; data and process modeling; ontology based approaches; variability and evolution; adaptation, preferences and query refinement; queries, matching and topic search; and conceptual modeling in action.